PUBLICATION PRODUCTIVITY OF MALAYSIAN AUTHORS AND INSTITUTIONS IN LIS - Yazit, Norhazwani; A.N., Zainab (Malaysian Journal of Library and Information Science, 2017)
The paper attempted to provide a “picture” of Malaysian LIS research and publications. The study aimed to show (a) the total number and spread of publications produced by Malaysian authors; (b) the active authors; (c) the authorship pattern; (d) the affiliation status of the authors; (e) the main channels used to publish; and (f) the subject covered by the published works. The study confined its scope to the publications produced between 1965 and 2005 by Malaysian authors published in Malaysia as well as abroad. Bibliometric techniques and regression analysis were employed as the measuring instrument. The data was collected from seven online databases and seven well established library OPACs, which are expected to hold earlier and current LIS publications. A bibliometric toolbox was used to feed in text files which provided brief summaries of ranked results, a bibliograph and minimal Bradford zonal analysis. The subject categorization used by Gorman and Corbit’s Model of core competencies for LIS was used to categorized entries by subjects. The results indicated that (a) Malaysian LIS authors preferred to publish in journals (511, 48.9%) and conference papers (474, 45.4%); (b) the publication distribution fluctuated over the 41 year period but the moving average depicted a steady incremental trend; (c) a total of 506 authors contributed to 1,045 publications and 309 are one-time authors’ (d) the active authors in LIS are affiliated to 131 institutions and the productive institutions were the national Library of Malaysia, University of Malaya library and the academics at the MLIS Programme, University of Malaya.; (e) publication productivity was related to institutional active involvement in LIS journal publishing; and (f) the main subject areas actively researched upon were collection development and management, information centres and services, and ICT applications LIS.